Predictors for Long-Term Survival Free from Whole Brain Radiation Therapy in Patients Treated with Radiosurgery for Limited Brain Metastases - Gorovets, Daniel; Rava, Paul; Ebner, Daniel K.; Tybor, David J.; Cielo, Deus; Puthawala, Yakub; Kinsella, Timothy J.; DiPetrillo, Thomas A.; Wazer, David E.; Hepel, Jaroslaw T. (Frontiers in Oncology, 2015)
Purpose: To identify predictors for prolonged survival free from salvage whole brain radiation therapy (WBRT) in patients with brain metastases treated with stereotactic radiosurgery (SRS) as their initial radiotherapy approach. Material and Methods: Patients with brain metastases treated with SRS from 2001-2013 at our institution were identified. SRS without WBRT was typically offered to patients with 1-4 brain metastases, Karnofsky Performance Status ≥70, and life expectancy ≥3 mo. Three hundred and eight patients met inclusion criteria for analysis. Medical records were reviewed for patient, disease, and treatment information. Two comparison groups were identified: those with ≥1-yr WBRT-free survival (N=104), and those who died or required salvage WBRT within 3 mo of SRS (N=56). Differences between these groups were assessed by univariate and multivariate analyses. Results: Median survival for all patients was 11 mo. Among patients with ≥1-yr WBRT-free survival, median survival was 33 mo [12-107 mo] with only 21% requiring salvage WBRT. Factors significantly associated with prolonged WBRT-free survival on univariate analysis (p<0.05) included younger age, asymptomatic presentation, RTOG RPA class I, fewer brain metastases, surgical resection, breast primary, new or controlled primary, absence of extracranial metastatic disease, and oligometastatic disease burden (≤5 metastatic lesions). After controlling for covariates, asymptomatic presentation, breast primary, single brain metastasis, absence of extracranial metastases, and oligometastatic disease burden remained independent predictors for favorable WBRT-free survival. Conclusions: A subset of patients with brain metastases can achieve long-term survival after upfront SRS without the need for salvage WBRT. Predictors identified in this study can help select patients that might benefit most from a treatment strategy of SRS alone.